Automated Method for Optimizing Feasible Locations of Mobile Cranes Based on 3D Visualization. (2017) - Pan, Zaiyi; Guo, Hongling; Li, Yan
Abstract: The precise operation of mobile cranes contributes to the safety and efficiency of lift works, among which accurate location is one of the most critical aspects. Considering the complexities and dynamics of construction sites, this paper presents an approach for crane location determination based on the simulation of mobile crane operations. First a data processing method is developed to enable the automated conversion from BIM (Building Information Modeling) and schedule plan to the simulation system. Then the reachability and work radius of mobile cranes are examined for selecting the initial feasible location points. The bounding box method is used for the collision detection to ensure the safety of crane operations. Also, the minimum number of relocation and the lift time are taken into account to determine the final feasible location points of mobile cranes.